A Case Report of Rubinstein-Taybi Syndrome Presenting with Extensive Keloid Formation and Review of Literature - Kim, Jee-Woo; Ko, Jung Min; Lee, Dong Yoon; Shin, Jung-Won (Annals of dermatology, 2023)
Rubinstein-Taybi syndrome (RSTS) is an extremely rare genetic disorder affecting multi-organ systems. A tendency to form keloid is one of the common dermatologic manifestations. We describe a 23-year-old female presented with extensive keloids which developed spontaneously. She had typical facial features, broad thumbs, and dental defects, which were suspicious features of genetic syndrome. Direct sequencing for cyclic-AMP-regulated enhancer binding protein revealed a novel mutation. So far, 23 cases of RSTS have been reported in Korean literature. To the best of our knowledge, this is the first report in Korea to describe confirmed case of RSTS with extensive keloids as a chief manifestation.Rubinstein-Taybi syndrome (RSTS) is an extremely rare genetic disorder affecting multi-organ systems. A tendency to form keloid is one of the common dermatologic manifestations. We describe a 23-year-old female presented with extensive keloids which developed spontaneously. She had typical facial features, broad thumbs, and dental defects, which were suspicious features of genetic syndrome. Direct sequencing for cyclic-AMP-regulated enhancer binding protein revealed a novel mutation. So far, 23 cases of RSTS have been reported in Korean literature. To the best of our knowledge, this is the first report in Korea to describe confirmed case of RSTS with extensive keloids as a chief manifestation.